How AI impacts urban living and public health : 17th International Conference, ICOST 2019, New York City, NY, USA, October 14-16, 2019, Proceedings /: 17th International Conference, ICOST 2019, New York City, NY, USA, October 14-16, 2019, Proceedings. (2019) - Unknown
No abstract available